Metabolic Syndrome and Cardiovascular Risk Factors in Hypertensive Patients ≤ 65 years of Age - Kadhum, Zainab Salim; Raghib Ali, Dr. Kawther Mohammed; Mahdi Al, Dr.Suha Abdulkareem (Academic Journal of Clinicians, 2025)
Background: Metabolic syndrome in hypertensive patients, it has been observed, during the long-term follow-up of patients with arterial hypertension (AHT), an increase in cardiac and cerebrovascular complications by 40% in those diagnosed with MS compared to those who did not have it. Objective: To ascertain the metabolic syndrome prevalence in hypertensive patients with in the age of ≤65 years old and other cardiovascular risk and to examine its correlation with the level of blood pressure regulation. Patients and method: A descriptive observational cross-sectional study was carried out in patients aged between 18 and 65 years, both inclusive, diagnosed with arterial hypertension previously, who granted their consent to participate in the study once informed of the objectives of the same. Those with physical, mental limitation or concurrent illness that made it impossible to answer the questionnaire were excluded, as well as those who refused participation once informed of the objectives of the study. Results: The mean age of the participants was 57.6 years (SD: 6.5), with an age range between 37 and 65 years. The characteristics of the participants according to sex, although there were no statistically significant differences (42.5% in males and 38.05% in females). Considering the 2001 ATP III and IDF definitions, 38.2% (95% CI: 32.2%-44.21%) and 42.7% (95% CI: 36.6%-48.8%) met metabolic syndrome criteria, respectively Conclusion: The current study show that 40.4% of the hypertensive patients were suffer from metabolic syndrome, regardless of the criteria used, and more than two thirds have abdominal obesity, Furthermore, we determined that metabolic syndrome is not merely a modifier of cardiovascular risk but should also be regarded in the management of blood pressure in hypertensive individuals, alongside therapeutic adherence, comorbidities, and physical activity